Resumo Acadêmico: uma experiência mediativa com o gênero na formação docente inicial - Bragagnollo, Rubia Mara [UNESP]; Menegassi, Renilson José (Universidade Estadual de Maringa, 2014)
Current research deals with the constitution of writing in initial teacher training when employing the Academic Summary genre. The mediation process and the tools involved are focused. Analysis is based on the concepts of interaction and writing discussed by Vygotsky (1991), Bakhtin and Volochinov (2006) and Bakhtin (2003) within the socio-interaction and enunciation perspectives of language and the notion of discursive genres. A mediation experience in the writing of academic summaries with teachers in initial training at the university and the highlighting of mediation in this process are provided. The experience occurred with first year students of the Language and Literature undergraduate course at a government-run university in Paraná in 2009. Employing the qualitative-interpretative approach in the analysis of one summary, the advantages of mediation activities inwriting process of the genre are demonstrated.
Academic summary: A mediation experience with the genre in initial teacher training
Keywords: Academic writing; Mediation; Textual genres